2021
DOI: 10.1177/13684302211040865
|View full text |Cite
|
Sign up to set email alerts
|

Prejudicial reactions to the removal of Native American mascots

Abstract: As Native American mascots are discontinued, research is needed to understand the impact on intergroup relations. Such discontinuations may be threatening to some and increase prejudice against Native Americans. In Study 1 ( N = 389), exposure to information about a Native American mascot removal increased punitive judgments against a Native American in a hypothetical legal scenario, particularly among those high in racial colorblindness and those residing in the implicated geographical location. Study 2 ( N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
1
12
1
Order By: Relevance
“…There are two possible explanations for this drop: First, the 2020 BLM protests could have caused the drop. This would align with situational models of bias, which predict that changes in the social and cultural environment should lead to changes in bias (Jimenez et al, 2021;Ofosu et al, 2019;Payne et al, 2017). Initially, we had expected that this change in bias would take place gradually over timeas it did in response to Trump's election (Charlesworth & Banaji, 2022).…”
Section: Effects Of Blm On Racial Bias 20mentioning
confidence: 54%
See 1 more Smart Citation
“…There are two possible explanations for this drop: First, the 2020 BLM protests could have caused the drop. This would align with situational models of bias, which predict that changes in the social and cultural environment should lead to changes in bias (Jimenez et al, 2021;Ofosu et al, 2019;Payne et al, 2017). Initially, we had expected that this change in bias would take place gradually over timeas it did in response to Trump's election (Charlesworth & Banaji, 2022).…”
Section: Effects Of Blm On Racial Bias 20mentioning
confidence: 54%
“…The drop in implicit bias seems robust to changes in age, gender, and political orientation: There is a drop for 5 of 7 political orientation scale points spread across the full political orientation spectrum. Of course, we cannot rule out changes in unobserved demographics as explanation for the drop in biasa limitation we share with most published results on the development of bias over time (Charlesworth & Banaji, 2022;Ofosu et al 2019;Jimenez et al, 2021).…”
Section: Effects Of Blm On Racial Bias 20mentioning
confidence: 82%
“…Prior studies have also suggested that the Native American IAT provides meaningful information about prejudice. Specifically, Jimenez et al (2021) found that prejudicial backlash against the removal of Native American sports mascots was observed in regional data collected via the Native American IAT. Again, we retrieved explicit bias data, which is measured using adapted items from the anti-Black explicit bias measure, and computed state averages ( N = 19,067; see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it will be important to examine judgments of discrimination against Indigenous people in future research. Given the prevalence of both historical and contemporary anti-Indigenous prejudice and discrimination, one might expect that Indigenous people should be a relatively close fit to the target prototype (e.g., Feagin, 2014;Findling et al, 2019;Jimenez et al, 2023;Loewen, 1995). However, given that Indigenous people are often treated as "invisible," we suspect that they may not be a close fit to the target prototype held in the broader U.S. culture and that discrimination against Indigenous people may be poorly recognized (e.g., Davis-Delano et al, 2021;Fryberg & Eason, 2017;Lopez et al, 2022).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%